Acute limb ischemia of traumatic origin: arterial contusion thrombosis - Ríos Bruno, Guaymirán; Nusspaumer, Federico; Campos Pierri, Néstor C (Cirugía del Uruguay, 2021)
The paper presents one observation of arterial traumatism of the lower limb, due o contusion, associated with arterial thrombosis. Stress is laid on the fact that its treatment is urgent, and that it is essential that the surgeon have an exact knowledge of the surgical tactics. In this manner amputation or serious functional sequela will be avoided.